Evolutionary developmental genetics of fruit morphological variation within the Solanaceae - Wang, Li; Li, Jing; Zhao, Jing; He, Chaoying (Frontiers in Plant Science, 2015)
Morphological variations of fruits such as shape and size, and color are a result of adaptive evolution. The evolution of morphological novelties is particularly intriguing. An understanding of these evolutionary processes calls for the elucidation of the developmental and genetic mechanisms that result in particular fruit morphological characteristics, which determine seed dispersal. The genetic and developmental basis for fruit morphological variation was established at a microevolutionary time scale. Here, we summarize the progress on the evolutionary developmental genetics of fruit size, shape and color in the Solanaceae. Studies suggest that the recruitment of a pre-existing gene and subsequent modification of its interaction and regulatory networks are frequently involved in the evolution of morphological diversity. The basic mechanisms underlying changes in plant morphology are alterations in gene expression and/or gene function. We also deliberate on the future direction in evolutionary developmental genetics of fruit morphological variation such as fruit type. These studies will provide insights into plant developmental processes and will help to improve the productivity and fruit quality of crops.